INCLUSIVE INNOVATION AND KNOWLEDGE MANAGEMENT IN THE HAKU WIÑAY PROJECT PROJECT ATTACHED TO FONCODES - Wong Copaja, Edgard Enrique (2025)
Recent studies have separately analyzed the importance of inclusive innovation and knowledge management. This document provides a clear view of the characteristics of each variable and the links between them, so that each variable can be analyzed and summarized separately for each entrepreneur. The objective is to identify if there is a relationship between inclusive innovation through knowledge management, as demonstrated by the users of the Haku Wiñay project. The study faced some limitations, such as the dispersion of the population and its relationship with the Andean highland region, where the users were not located in a single place, remaining in the countryside in the morning and in their homes in the afternoon, which increased the data collection time to five months, and the researchers took into account the entire population, that is, 80 entrepreneurs, and 100% of the data was collected. The data was collected through interviews with each company. It was concluded that the main characteristics of participatory innovation can be identified through the knowledge management of the users of the Haku Wiñay project.